Capability of contrast enhanced magnetic resonance tomography in accurate grading of chondrosarcoma - A. V. Fedorova; N. V. Kochergina; I. V. Boulytcheva; E. A. Sushentsov; A. S. Nered; Y. A. Shchipakhina; A. B. Bludov (Бюллетень сибирской медицины, 2018)
Chondrosarcoma is one of the most common tumors in adults. Correct grading of chondrosarcoma is the most important criterion that defines the course of surgical treatment. A case report of a 56 years old female patient with chondrosarcoma of the pelvic bone is presented. The assistance of magnetic resonance tomography in accurate grading of the tumor is shown.